Sensor and data fusion a tool for information assessment and decision making - Klein, Lawrence A. (SPIE Press, 2004)
This book illustrates the benefits of sensor fusion by considering the characteristics of infrared, microwave, and millimeter-wave sensors, including the influence of the atmosphere on their performance. Applications that benefit from this technology include: vehicular traffic management, remote sensing, target classification and tracking- weather forecasting- military and homeland defense. Covering data fusion algorithms in detail, Klein includes a summary of the information required to implement each of the algorithms discussed, and outlines system application scenarios that may limit sensor size but that require high resolution data.
Keywords: Signal processing -- Digital techniques.; Multisensor data fusion.; elektronické knihy; electronic books